Impact of liquidity on banks’ productivity: A study on selected commercial banks in Bangladesh - Chaudhury, Nazneen Jahan (IIUC Studies, 2020)
Financial institutions are the directories responsible for allocating liquidity to its most productive uses. A bank’s liquid assets are significant not only for defending a bank against definite kinds of distresses but also increasing its productivity. This study analyzes the influence of liquidity on banks’ productivity throughout the time period 2007-2016. The study is curbed to five Commercial Banks enlisted under Stock Exchanges in Bangladesh. Here the researcher has taken only the secondary data into account. The outcomes of the study substantiate the hypothesis that Liquidity and Productivity are both positively and significantly correlated. The liquidity management of bank is the administration of fund flowing into and out of the bank in a way that will maintain profitability, solvency, liquidity and productivity. The management of a commercial bank ought to be efficient in order to fulfill these objectives. To attain the aforementioned objectives, a feasible structure has been built up to direct banks’ liquidity management in accordance with the attached guidelines, global standards and greatest practices. IIUC Studies Vol.15(0) December 2018: 59-71